THE LAST RAVEN - Thomas, Craig, 1942-2011 (New York, : HarperPaperbacks, 1990)
"When the CIA and the KGB conspire to shoot down one of the Soviet Union's most important reforming politicians, what ensues is a massive coverup operation to disguise the event as an accident."